Additively manufactured Raney-type Copper catalyst for methanol synthesis - Heßelmann, Christina; Wolf, Torsten; Galgon, Florian; Körner, Carolin; Albert, Jakob; Wasserscheid, Peter (Catalysis: Science and Technology, 2020)
We describe a novel approach to prepare cellular RANEY (R)-type catalysts by combining additive manufacturing (AM) of a Cu-Al alloy followed by selective leaching of Al with aqueous NaOH solutions. Three-dimensional cellular geometries of Cu-70Al were fabricated by laser-metal-deposition (LMD). After activation by an optimized leaching process, highly active and selective catalytic structures for CO hydrogenation to methanol were obtained.
CRIS-Team WoS Importer:2020-01-17

A Novel Approach for Rapid Material Library Generation Using Laser-Remelting - Gaag, Tobias; Heidowitzsch, Maximilian; Galgon, Florian; Körner, Carolin; Zenk, Christopher (Advanced Engineering Materials, 2024)
Cost- and time-demanding trial-and-error methods have been the historical route for alloy development. A combinatorial approach can significantly simplify and accelerate the development process by characterization of composition dependent properties on material libraries, which are specimens or sets of specimens that map out a certain composition space, often employing composition profiles. Herein, a promising production method for such a material library is proposed: laser-remelting of stacked blocks of different compositions is evaluated for its suitability to produce material libraries, using the ternary CrCoNi system for a proof-of-concept. The composition profiles of the successfully created CrCoNi material library were measured by electron probe micro analysis. The intermixing has a length of about 2.5 mm. An analytical model describing the intermixing process is proposed and shows value in the estimation of the intermixing length after the first melting step. The comparison of the experimental microstructure observations from this work and from literature shows mostly good agreement with some deviations related to microsegregation and finite quenching cooling rates, which is supported by thermodynamic calculations regarding phase stability. In the single-phase region, the mechanical properties as measured via microhardness indentation are discussed as potential candidates for model validation.
CRIS-Team Scopus Importer:2024-02-16
Keywords: combinatorial alloy development; CrCoNi; high-throughput analysis; material library; multi-principal-element-alloy; phase diagram

Growth and coarsening kinetics of gamma prime precipitates in CMSX-4 under simulated additive manufacturing conditions - Wahlmann, Benjamin; Galgon, Florian; Stark, Andreas; Gayer, Sören; Schell, Norbert; Staron, Peter; Körner, Carolin (Acta Materialia, 2019)
Additive manufacturing of superalloys offers new opportunities for alloy design but also poses significant processing difficulties. While the γ′ phase is responsible for the excellent high-temperature resistance of these alloys, it also induces cracking by precipitation hardening during manufacturing. Using small-angle X-ray scattering, we characterized the dynamic precipitation, dissolution, coarsening, and morphological evolution of the γ′ phase in situ during simulated additive manufacturing conditions. For this purpose, a CMSX-4 cylinder was subjected to cyclic heat treatment with heating and quenching rates up to 300 K/s. A specialized setup employing aluminum lenses to focus the X-ray beam was utilized to extend the q-range to small scattering vectors up to 0.035 nm-1. It was shown that the γ′ phase precipitates extremely fast without any measurable undercooling but remains below the equilibrium fraction throughout the process. Coarsening is readily measurable over timespans of only several seconds. A fraction of the γ′ phase that was dissolved during heating reprecipitated by forming new particles instead of growing on already existing precipitates. The findings provide new insight into the dynamic behavior of the γ′ phase during additive manufacturing and may prove valuable in designing new superalloys and processing strategies for additive manufacturing.
Keywords: Ni-base superalloys; Phase transformations; X-ray synchrotron radiation; Nucleation and growth; Additive manufacturing

Microstructural evolution and mechanical properties in Zr–Cu–Al–Nb bulk metallic glass composites prepared by laser metal deposition - Luo, Ning; Galgon, Florian; Krauß, Sebastian; Morales, Luis A.; Merle, Benoit; Zenk, Christopher; Körner, Carolin (Intermetallics, 2022)
In this work, laser metal deposition (LMD), a direct energy deposition (DED) additive manufacturing technology, is used to prepare Zr59.3Cu28.8Al10.4Nb1.5 bulk metallic glass composites (BMGCs). Phase constitutions and thermal behavior of LMD-processed Zr–Cu–Al–Nb samples are examined using X-ray diffraction (XRD) and differential scanning calorimetry (DSC). The microstructure evolution parallel to the build direction is characterized in detail utilizing scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), electron probe microscopy analysis (EPMA) and electron backscatter diffraction (EBSD). Young's modulus and hardness in typical microstructures are evaluated employing nanoindentation. Within each deposited layer, a periodic microstructure, exhibiting crystalline features of three distinctly different morphologies, is observed, depending on the location within that layer. Along the build direction, the dominating microstructure of the melt pool evolves from a nearly featureless amorphous state over fine nanocrystals to coarse nanocrystals while the morphology of most micro-scale dendritic crystals changes from flower-shaped to columnar, simultaneously a coarse microstructure appearing in upper layers. The fine Al-rich phases gradually coarsen directionally parallel to the build direction. Furthermore, the correlation between microstructure and mechanical properties is investigated. This work enhances our knowledge about microstructural characteristics and mechanical properties of BMGCs in-situ fabricated by DED additive manufacturing.
Created from Fastlane, Scopus look-up
Keywords: Bulk metallic glass composites; Crystallization; Laser metal deposition; Microstructure; Nanoindentation

Microstructure and mechanical properties of a laser-based directed energy deposited Mo-Si-Ti alloy - Schliephake, Daniel; Ramdoss, Sri R.; Vikram, R. J.; Falcão, Gabriely; Galgon, Florian; Thota, Hemanth; Hinrichs, Frauke; Zenk, Christopher; Kauffmann, Alexander; Eggeler, Yolita; Suwas, Satyam; Schwaiger, Ruth; et al. (Journal of Materials Science, 2025)
This study focuses on the linkage between microstructure and mechanical properties at elevated temperatures of a Mo-20Si-52.8Ti (at.%) eutectic alloy produced by directed energy laser deposition (DED-LB). The alloy consists of a body centered cubic solid solution (Mo,Ti,Si)ss and a hexagonal (Ti,Mo)5Si3 phase. In addition, a conventional as-cast (AC) alloy with subsequent heat treatment (HT) to further coarsen the microstructure is investigated to rationalize the effect of microstructural length scale on mechanical properties by DED-LB. The fine microstructure produced by DED-LB has a significant effect on the 0.2% offset yield strength at 900 °C compared to AC and HT. This was found to be mainly due to the depletion of Si in (Mo,Ti,Si)ss and to the creep contribution caused by the high phase boundary density. By contrast, the effect of interstitial O contamination and texture formation in the (Ti,Mo)5Si3 phase is excluded as a reason of the difference in 0.2% offset yield strength compared to AC and HT.
CRIS-Team Scopus Importer:2025-07-18

Miniature mechanical testing of LMD-fabricated compositionally & microstructurally graded γ titanium aluminides - Galgon, Florian; Melzer, Daniel; Zenk, Christopher; Dzugan, Jan; Körner, Carolin (Journal of Materials Research, 2022)
The design freedom in Laser Metal Deposition provided by the absence of a powder bed enables the fabrication of Functionally Graded Materials through Additive Manufacturing. For the first time, two suitable γ-TiAl alloys (TiAl48Cr2Nb2, TiAl45Nb4C) are combined in direct and gradual transitions to generate different microstructure morphologies and, consequently, different mechanical properties within a component after an identical heat treatment. The influence of alloy composition, microstructure type, and material transition on the tensile properties and fracture toughness is analyzed through miniature testing. Miniature tensile tests show no orientation dependency in regard to the build direction and the composition/microstructure transition is not found to be a preferred fracture site. The miniature fracture toughness tests reveal that already small composition changes—insufficient to alter the microstructure configuration—can have a significant effect on the cracking behavior. Graphical abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2022-11-25
Keywords: Directed energy deposition; Fracture toughness; Functionally graded materials; Laser metal deposition; Miniature testing; Tensile testing; Titanium aluminides

Preparation of Fe-Co-B-Si-Nb bulk metallic glasses by laser powder bed fusion: Microstructure and properties - Luo, Ning; Scheitler, Christian Josef; Ciftci, Nevaf; Galgon, Florian; Fu, Zongwen; Uhlenwinkel, Volker; Schmidt, Michael; Körner, Carolin (Materials Characterization, 2020)
In this work, laser powder bed fusion (LPBF) was employed for the preparation of (Fe0.6Co0.4)0.75B0.2Si0.0596Nb4 bulk metallic glasses (BMGs). Microstructural evolution, thermal stability and mechanical properties of LPBF-processed samples using different laser power and scanning speed were systematically investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM), electron probe microscopy analysis (EPMA), electron backscatter diffraction (EBSD), differential scanning calorimetry (DSC) and nanoindentation. The results show that low area energy input facilitates the formation of Fe-Co-B-Si-Nb BMGs with a large amorphous fraction. LPBF-processed sample with an area energy density of 1.25 J/mm2 (at a laser power of 60 W and a scanning speed of 600 mm/s) exhibits a nearly fully glassy microstructure with an amorphous fraction of approximately 99%, meanwhile possessing almost identical characteristic temperatures and enthalpy of crystallization as the as-atomized powder. The microstructure and mechanical properties of LPBF-processed samples are correlated with the processing parameters during LPBF. This work demonstrates that LPBF is a promising method to prepare fully amorphous Fe-Co-B-Si-Nb BMGs. The results provide key insights for the fabrication of BMGs and BMGs composites with the desired microstructure and properties by additive manufacturing.
CRIS-Team Scopus Importer:2020-03-06
Keywords: Amorphous fraction; Bulk metallic glasses; Crystallization; Laser powder bed fusion; Microstructure; Nanoindentation